Analysis Of Smoking Behavioral Factors In Adolescents During Covid-19 Pandemic In Aru Islands Maluku - Wakim, Novalin; Saputri, Milla Evelianti; Helen, Milya (Journal Of Nursing Practice, 2021)
Background: Smoking has become a habit of Indonesian society. This behavior is not only found in adults but also in adolescents over 15 years. Indonesia ranks third out of the ten largest smoking countries in the world. There are 33.37% of the population of the Aru Islands aged over 15 years who have a smoking habit. This behaviour in adolescents occurs due to invitations from peers, being ridiculed by friends if they do not smoke, desire to try new things, fad, addicted, imitating parents and the influence of the mass media.Purpose: This study aimed to determine the factors of smoking behaviour in adolescents in Aru Islands, Maluku.Methods: This study used a cross sectional approach with a total sample of 72 respondents using purposive sampling technic. This research used questionnaire as instrument, whereas the data were analysed using the chi-square test to relate the analysed data to the chi-square of age, education, knowledge, and stress levels.Results: The results shows that there are relationships between age (p. value 0.015), education (p. value 0.005), knowledge (p. value 0.038) and stress levels (p. value 0.035) on smoking behaviour in the Aru Islands region, Maluku.Conclusion: The hope is that with good education and knowledge, teenagers in these areas will be more easily exposed to information about the dangers and impacts of smoking at a young age and not use cigarettes as an escape to deal with stress